Kesedaran membayar zakat pendapatan di kalangan kakitangan profesional Universiti Kebangsaan Malaysia - Mohd Ali Mohd Nor; Hairunnizam Wahid; Nor Ghani Md. Nor (Penerbit Universiti Kebangsaan Malaysia, 2004)
It is perceived that the awareness on a duty to pay zakat on income by Muslim professionals is still marginal as been reported by MAWIP. The percentage of payment can be improved if they are being educate with the important of it, a better law being imposed and a credibility of MAWIP being improved. There exist also some professionals who have their own reasons not to pay at all. This situation actually should not occur because the responsibility to pay zakat on income must be the utmost priority as compared to that of an income tax. Thus, this study aims to identify the factors the affect the payment of zakat on income by the professionals level looking from the locational, demographic, accomodation and educational perspectives and to directly identify the most significant factors that affect. This study uses a logit binomial model to test the variable under controlled. The result shows that iman and religious education are the most significant factors that influence the payment of zakat on income. A few suggestions are also being made to ensure the awareness among the zakat payers increases in the near future